Allometry of exaggerated mandibular tusks in the burrowing mayfly Rhoenanthus coreanus (Ephemeroptera: Potamanthidae). Issue 5 (16th March 2021) - Mayorga, Alfredo; Bae, Yeon Jae
Abstract: Exaggerated morphological traits, such as the mandibular tusks of mayflies, are rarely observed in immature insects, especially when such traits are exhibited by both sexes. The aim of the present study was to investigate the static allometry, sexual size dimorphism, and trade‐offs (i.e. compensations) of exaggerated mandibular tusks in the larvae of Rhoenanthus coreanus (Yoon & Bae) (Ephemeroptera: Potamanthidae). As expected, sexual dimorphism was observed in size, especially in that of eyes and tusks, with males exhibiting significantly larger eyes and females exhibiting longer tusks. Tusk size was monomorphic in males, and in contrast to that reported in previous studies, the static allometry of tusks was positive in females but negative in males. A positive compensation and correlation was observed between tusk and foreleg length in both sexes, which may be related to the burrowing and feeding behavior.